Desarrollo de un sensor de calidad de vapor. - Andrade Rosales, Edda G. (Comisión Nacional de Energía Atómica. Instituto Balseiro, 2017)
Fil. Andrade Rosales, Edda G.. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina